2004
DOI: 10.1016/j.femsec.2004.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Structure and activity of the nitrate-reducing community in the rhizosphere of Lolium perenne and Trifolium repens under long-term elevated atmospheric pCO2

Abstract: Rhizosphere soil was sampled in monocultures of Lolium perenne and Trifolium repens in June and October 2002, at two different nitrogen fertilisation levels (14 and 56 g N m(-2) year(-1)) and under two pCO(2) atmospheres (360 and 600 ppmv) at the Swiss FACE (Free Air Carbon dioxide Enrichment) site. Directly extracted soil DNA was analysed with restriction fragment length polymorphism (PCR-RFLP) by use of degenerated primers for the narG gene encoding the active site of the membrane-bound nitrate reductase. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
27
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(36 citation statements)
references
References 31 publications
6
27
3
Order By: Relevance
“…We hypothesize that the long-term fertilization effect was, at least partially, attributable to an indirect effect by soil acidification, which has resulted in a selection of bacteria adapted to low pH after 20 years of fertilization with acid generating ammonium salts also suggest this. Recently, it has been shown that pH can affect the composition of the denitrifying communities in soil (9). However, no strong relationship between soil pH and the measurements of microbial activity was observed in our study.…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…We hypothesize that the long-term fertilization effect was, at least partially, attributable to an indirect effect by soil acidification, which has resulted in a selection of bacteria adapted to low pH after 20 years of fertilization with acid generating ammonium salts also suggest this. Recently, it has been shown that pH can affect the composition of the denitrifying communities in soil (9). However, no strong relationship between soil pH and the measurements of microbial activity was observed in our study.…”
Section: Discussioncontrasting
confidence: 95%
“…All sequences from the specific RFLP pattern types (9,14,16,19) in the clone library from soil fertilized with (NH 4 ) 2 SO 4 (D) clustered together in the phylogram (Fig. 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have shown that potential denitrifying enzyme activity may be stable or decrease (Hungate et al, 1997;Barnard et al, 2004), whereas N 2 O emissions may increase (Arnone and Bohlen, 1998;Baggs et al, 2003a,b) for herbaceous systems under elevated pCO 2 . Little is known about the response of microorganisms involved in denitrification (Roussel-Delif et al, in press;Deiglmayr et al, 2004), partly because of the widespread ability to denitrify, and functional differences among denitrifying microorganisms make it difficult to relate denitrification activity to soil microbial communities (Cavigelli and Robertson, 2001). Roussel-Delif et al (in press) recently showed that the frequency of root-associated nitrate-dissimilating Pseudomonas (NDP) in low fertilised (14 g N m K2 y K1 ) L. perenne swards was increased under elevated pCO 2 , suggesting that increased pCO 2 provided favourable conditions for the dissimilation of nitrate and related organisms.…”
Section: Introductionmentioning
confidence: 99%
“…This method also better predictor of similarities or dissimilarities (Marilley 1999;Hebeisen 1997;Deiglmayr 2006;Caradus 1986;Caradus 1992). Table 3 show that describing more than 70%, cumulative percent plant characteristics should be examined in five groups (Eigen value: 1,1254, proportion:0,080,cumulative percent: 76,1%).…”
Section: Flowermentioning
confidence: 98%